Implementation of multi-component Zhdanov closure in SOLEDGE3X. (1st May 2022) - Bufferand, H; Balbin, J; Baschetti, S; Bucalossi, J; Ciraolo, G; Ghendrih, Ph; Mao, R; Rivals, N; Tamain, P; Yang, H; Giorgiani, G; Schwander, F; et al.
Abstract: The multi-component fluid closure derived by Zhdanov (2002 Transport Processes in Multicomponent Plasma (London: Taylor and Francis)) is implemented in the fluid code SOLEDGE3X-EIRENE to deal with arbitrary edge plasma composition. The closure assumes no distinction between species such as light versus heavy species separation. The work of Zhdanov is rewritten in a matricial form in order to clearly link friction forces and heat fluxes to the different species velocities and temperature gradients.